Rettegés a tradíciótól : Magyarország viszonya a protokollhoz - Koudela, Pál (Közép-Európai Közlemények, 2015)
Long development and regular practice leads to the simplification and unification of ceremonies' protocol even in Hungary. This is hard to shape regional differences in general; most of the books and textbooks can only suggest this vaguely in case of Hungary. The mystification of non-governmental relationships with countries of long tradition expresses the submissive character of Hungarian self-definition. The self-definitional fear from having no tradition is found in other different developed countries I use in this article as examples to outline regional characters of relation-ships with protocol. This approach fits to the historical and regional self-image of Hungary and to the uncertainty of Central Europe concepts. To help the understanding of geopolitical and cultural position of East Central Europe I collect different dimensions like definitions, historical and geographical approaches to conclude that there is no coherence in them. The lack of characterization urges us to find way and virtual nation concepts give a chance for new possibilities in such fragments as relationship to protocol.